Desain Smart Delivery Box : Sterilisasi Otomatis dan Notifikasi Real-Time Berbasis Arduino Mega 2560 - Retno Devita; Nanda Tommy Wirawan; Altof Fito (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The increase in online buying and selling due to government appeals during the Covid-19 pandemic has created a new habit in society, which also serves to reduce physical contact and prevent the spread of the virus. However, with the increase in delivery of goods, challenges arise in maintaining the cleanliness and safety of received packages. To address this, a smart package receiving system was developed that features automatic sterilization using ultraviolet (UV) lights and disinfectant spraying on incoming packages. This system aims to prevent the transmission of viruses that may be attached to the package. In addition, the system helps monitor and secure packages, especially when the owner is not at home. The system uses a microcontroller as the control center, equipped with an ESP32-CAM camera to document photos of the sender, as well as an ultrasonic sensor to detect whether the package is in the box or not. The process starts when the courier presses the “there is a package” button, which sends an OTP code to the receiver's Telegram. The courier enters the OTP code, places the package in the box, and closes it. After that, the UV lamp turns on for sterilization, the ESP32-CAM photographs the package, and the ultrasonic sensor detects the package status. If the package is detected, a photo notification of the sender is sent to Telegram, informing the recipient that the package is ready for pickup.